Poliomyelitis Survivors in the Time of a COVID-19 pandemic (SARS CoV-2) (Research, Society and Development, 2022)
Acute Anterior Poliomyelitis left sequelae on survivors, making them need continuous treatments, making them possibly vulnerable in the COVID-19 Pandemic. This study aims to analyze the prevalence of risk factors for contracting COVID-19 as well as developing the severe form among patients with Poliomyelitis Sequelae and Post Poliomyelitis Syndrome (PPS). An epidemiological study was carried out with an online questionnaire addressing epidemiological, physical and psycho-emotional health issues. For analysis, the Chi-square test was used. A total of 383 responses were obtained, divided into: Sequelae of Poliomyelitis (GP-49%;n=190) and PPS (GSPP-50.4%;n=193). Female gender and the age group 50-59 years were more prevalent in both groups. The most frequent involvements were monoparesis (38.9%GP; 21.7%GSPP), paraparesis (18.9%GP) and tetraparesis (16.6%GSPP). As for comorbidities, 37.4%GP and 37.3%GSPP reported Hypercholesterolemia; 42.6% GP and 47.1% GSPP Hypertension and 19.5% GP and 14.5% GSPP Diabetes. In the physical aspects, 57.9% (GP) and 65.8% (GSPP) reported worsening in quarantine and 19.7% (GSPP) and 7.9% (GP) need external help in activities. Poliomyelitis survivors are more vulnerable to contracting COVID-19 as well as manifesting the severe form of the disease due to their previous physical conditions and the comorbidities they present.